On the almost Gorenstein property of determinantal rings. Issue 3 (4th March 2018) - Taniguchi, Naoki
ABSTRACT: In this paper, we investigate the question of when the determinantal ring R over a field k is an almost Gorenstein local/graded ring in the sense of [14 ]. As a consequence of the main result, we see that if R is a non-Gorenstein almost Gorenstein local/graded ring, then the ring R has a minimal multiplicity.